Stable Transformant of Phalaenopsis amabilis Somatic Embryo Carrying 35S::AtRKD4 Develops Into Normal Phenotype of Transgenic Plant - Naufal Ghozi Aditya Perdana; Windi Mose; Muhammad Dylan Lawrie; Jose Gutierrez-Marcos; Endang Semiarti (Journal of Tropical Biodiversity and Biotechnology, 2021)
Phalaenopsis amabilis (L.) Blume orchid is an Indonesian national flower. The number of these orchids in their natural habitat is very limited, therefore plant propagation efforts are needed. One of the promising methods is plant propagation by inserting embryo gene AtRKD4 from a model plant Arabidopsis thaliana into the orchid genome to produce many somatic embryos. From previous research, we have obtained 28 plant P. amabilis transformants carrying the AtRKD4 gene, however, it was unknown whether these plants have normal phenotypes and growth similar to their parents. Therefore, descriptions on growth and morphology are needed. This research aimed to evaluate the phenotype of P. amabilis carrying 35S::AtRKD4 the transformants grown in greenhouse. To achieve it, AtRKD4 gene integration stability on transformants genome was analyzed. Morphology and cross-section anatomy structure on transformant and non-transformant plantswere described. The stability of AtRKD4 gene integration in the plant genome was confirmed by amplification of the AtRKD4 gene from genomic DNA with Polymerase Chain Reaction (PCR) using a specific primer for AtRKD4 and ACTIN genes as the internal control. The quantitative data from morphology and anatomy measurements were analyzed statistically using ANOVA. The results showed that AtRKD4 was stably integrated into the genome of P. amabilis transformants and all transformant plants showed similar morphology and anatomy characteristics as non-transformant plants. The AtRKD4 embryo gene was stably integrated into the orchid genome and the transformant plants grow normally without significant changes in phenotype.